Variability and relationships among forage yield and quality traits in pearl millet - Rai, Kedar N.; Blümmel, Michael; Singh, A.K.; Rao, A.S. (Global Science Books, 2012)
Pearl millet [Pennisetum glaucum (L.) R. Br.], owing to its high photosynthetic efficiency and biomass production ability, fewer disease and insect pest problems, and tolerance to multiple environmental stresses, is a valuable forage crop, especially in view of climate change consequences. Nine open-pollinated varieties (OPVs) and 27 top-cross hybrids made on three male-sterile lines (A-lines) were evaluated in Alfisols at ICRISAT, Patancheru in the rainy season for two years. When harvested at 50 days after sowing, top-cross hybrids out- yielded OPVs, on an average, by about 30%, most likely due to relatively earlier flowering and higher biomass accumulation. At 80 d harvest, the dry forage yield of OPVs was similar to those of the hybrids. Forage nitrogen (N), in vitro digestibility and metabolizable energy content were used as laboratory fodder quality traits. Significant differences among the OPVs and among the hybrids were observed for these three quality traits, both at 50 d and 80 d harvest. While forage N declined by 49% at 80 d harvest, in vitro digestibility and metabolizable energy declined by 16-18%. At 50 d harvest, forage N content, in vitro digestibility and metabolizable energy were all significantly negatively correlated with forage yield both in OPVs and hybrids. At 80 d harvest, forage yield was not associated with any of the three quality traits in OPVs. In hybrids, forage yield was significantly negatively correlated with forage N content, while it was significantly positively correlated with the other two quality traits. These results indicate better prospects of combining high forage yield with high levels of in vitro digestibility and metabolizable energy in hybrids than in OPVs of pearl millet.